The effect of diapycnal mixing on the ventilation and CFC-11 uptake in the Southern Ocean - Gao, Yongqi; Drange, Helge (Advances in Atmospheric Sciences, 2004)
The Miami Isopycnic Coordinate Ocean Model (MICOM) is used to investigate the effect of diapycnal mixing on the oceanic uptake of CFC-11 and the ventilation of the surface waters in the Southern Ocean (south of 45°S). Three model experiments are performed: one with a diapycnal mixing coefficientKd (m2 s−1) of 2 × 10−7/N (Expt. 1), one withKd = 0 (Expt. 2), and one withKd = 5 × 10−8/N (Expt. 3),N (s−1) is the Brunt-Väisälä frequency. The model simulations indicate that the observed vertical distribution of CFC-11 along 88°W (prime meridian at 0°E) in the Southern Ocean is caused by local ventilation of the surface waters and westward-directed (eastward-directed) isopycnic transport and mixing from deeply ventilated waters in the Weddell Sea region. It is found that at the end of 1997, the simulated net ocean uptake of CFC-11 in Expt. 2 is 25% below that of Expt. 1. The decreased uptake of CFC-11 in the Southern Ocean accounts for 80% of this difference. Furthermore, Expts. 2 and 3 yield far more realistic vertical distributions of the ventilated CFC-waters than Expt. 1. The experiments clearly highlight the sensitivity of the Southern Ocean surface water ventilation to the distribution and thickness of the simulated mixed layer. It is argued that inclusion of CFCs in coupled climate models could be used as a test-bed for evaluating the decadal-scale ocean uptake of heat and CO2.
Keywords: Sørishavet; geofysikk; klimamodeller; klimatologi; oseanografi; strømmodeller

Accumulation variability derived from an ice core from coastal Dronning Maud Land, Antarctica - Kaczmarska, Marzena; Isaksson, Elisabeth; Karlöf, Lars; Winther, Jan-Gunnar; Kohler, Jack; Godtliebsen, Fred; Olsen, Lena Ringstad; Hofstede, Coen M.; Van Den Broeke, Michiel R.; Van De Wal, Roderik S. W.; Gundestrup, Niels (Annals of Glaciology, 2004)
A 100 m long ice core was retrieved from the coastal area of Dronning Maud Land (DML), Antarctica, in the 2000/01 austral summer. The core was dated to AD 1737 by identification of volcanic horizons in dielectrical profiling and electrical conductivity measurement records in combination with seasonal layer counting from high-resolution oxygen isotope (δ18O) data. A mean long-term accumulation rate of 0.29 ma–1w.e. was derived from the high-resolution δ18O record as well as accumulation rates during periods in between the identified volcanic horizons. A statistically significant decrease in accumulation was found from about 1920 to the present. A comparison with other coastal ice cores from DML suggests that this is a regional pattern.
Publisher: Cambridge University Press
Keywords: Dronning Maud Land; geofysikk; glasiologi; iskjerner; klimatologi